WAKTU KEDATANGAN PASIEN STROKE DI LIMA RUMAH SAKIT PEMERINTAH DI DKI JAKARTA DAN FAKTORFAKTOR YANG MEMPENGARUHINYA - Edi Prasetyo*, Salim Harris**, Freddy Sitorus**, Herqutanto*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION SEVERE OF DISEASE STROKE IS HAVENT TO RECOGNIZED BY SOCIETY INDONESIA UNTIL MUCH STROKE PATIENTS COME LATE TO HOSPITAL TO GET MEDICATION THIS CONDITION RESULTS NUMBER MORBIDITY AND HIGH MORTALITY IN RURAL AND ALSO URBAN